Internship Program As Alternative Education Based on Fitrah in Forming Children's Independence: Program Magang Sebagai Pendidikan Alternatif Berbasis Fitrah Dalam Membentuk Kemandirian Anak - Hasballah, Maria Ulfa; Khaira, Rizka (Halaqa: Islamic Education Journal, 2022)
Internships have a correlation with children's independence. Independence is the process of trusting children to be responsible for themselves. Independence can be reflected in the way of thinking, acting and guiding the world of education today, where knowledge must be followed by skills so that children can grow and develop independently. This research explores further related to child internship programs that can form children's independence. This research approach uses qualitative methods, with three research subjects. Data analysis used qualitative descriptive. The results of the study indicate that the apprenticeship learning process is indicated to be able to strengthen the learning culture that has been obtained by the child. This refers to the responses of the three subjects who answered that the internship culture was in accordance with the child's learning culture. The cultural harmony received by the child will make it easier for the child to assess the usefulness of the educational process for the child. Overall, the apprenticeship learning process has changed the aspects of the educational value applied to children. The results of the parents' assessment of the children participating in the internship program are that the children feel comfortable and are not burdened with participating in the internship. So that the independence process is well formed through the internship program.